Co-delivery of ccl19 gene enhances anti-caries DNA vaccine pCIA-P immunogenicity in mice by increasing dendritic cell migration to secondary lymphoid tissues - Yan Yan-hong; Qi Sheng-cai; Su Ling-kai; Xu Qing-an; Fan Ming-wen (Acta Pharmacologica Sinica, 2016)
Yan-hong YAN1, Sheng-cai QI2, Ling-kai SU1, Qing-an XU1, 3, *, Ming-wen FAN1, * 1The State Key Laboratory Breeding Base of Basic Science of Stomatology (Hubei-MOST) & Key Laboratory of Oral Biomedicine of Ministry of Education (KLOBM), School & Hospital of Stomatology, Wuhan University, Wuhan 430079, China; 2Center of Stomatology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, China; 3Department of Endodontics, School and Hospital of Stomatology, Wuhan University, Wuhan 430079, China Aim: To investigate how co-delivery of the gene encoding C–C chemokine ligand-19 (CCL-19) affected the systemic immune responses to an anti-caries DNA vaccine pCIA-P in mice. Methods: Plasmid encoding CCL19-GFP fusion protein (pCCL19/GFP) was constructed by inserting murine ccl19 gene into GFP-expressing vector pAcGFP1-N1. Chemotactic effect of the fusion protein on murine dendritic cells (DCs) was assessed in vitro and in vivo using transwell and flow cytometric analysis, respectively. BALB/c mice were administered anti-caries DNA vaccine pCIA-P plus pCCL19/GFP (each 100 μg, im) or pCIA-P alone. Serum level of anti-PAc IgG was assessed with ELISA. Splenocytes from the mice were stimulated with PAc protein for 48 h, and IFN-γ and IL-4 production was measured with ELISA. The presence of pCCL19/GFP in spleen and draining lymph nodes was assessed using PCR. The expression of pCCL19/GFP protein in these tissues was analyzed under microscope and with flow cytometry. Results: The expression level of CCL19-GFP fusion protein was considerably increased 48 h after transfection of COS-7 cells with pCCL19/GFP plasmids. The fusion protein showed potent chemotactic activity on DCs in vitro. The level of serum PAc-specific IgG was significantly increased from 4 to 14 weeks in the mice vaccinated with pCIA-P plus pCCL19/GFP. Compared to mice vaccinated with pCIA-P alone, the splenocytes from mice vaccinated with pCIA-P plus pCCL19/GFP produced significantly higher level of IFN-γ, but IL-4 production had no significant change. Following intromuscular co-delivery, pCCL19/GFP plasmid and fusion protein were detected in the spleen and draining lymph nodes. Administration of CCL19 gene in mice markedly increased the number of mature DCs in secondary lymphoid tissues. Conclusion: CCL19 serves as an effective adjuvant for anti-caries DNA vaccine by inducing chemotactic migration of DCs to secondary lymphoid tissues. Keywords: chemokine; CCL19; DNA vaccination; anti-caries DNA vaccine; dendritic cell; splenocyte; IFN-γ; IL-4; stomatology This study was supported by grants from the National Natural Science Foundation of China (No 81000435), the Doctoral Fund of the Ministry of Education of China (No 200804861011), and the PhD Candidates Self-research (including 1+4) Program of Wuhan University in 2010 (No 2010304010100163). * To whom correspondence should be addressed. E-mail fmw@whuss.com(Ming-Wen FAN); xuqingan1977@yahoo.com.cn (Qing-An XU) Received 2012-06-17 Accepted 2012-09-29